Linear Programming with Changing Coeffcients of Objective Function - Alaverdyan, Armen H. (Mathematical Problems of Computer Science, 2021)
The article studies the problem of linear programming, when the objective function’scoeffcients change depending on the data ow. The set of objective function coeffcients under which the vertex of the feasible set of linear programming is an optimal solution is described.